Visualizing and mapping two decades of literature on board of directors research: A bibliometric analysis from 2000 to 2021 - Wahyu Trinarningsih; Adhe Rizky Anugerah; Prafajar Suksessanno Muttaqin (Cogent Business & Management, 2021)
The Board of Directors (BOD) plays an important role in determining the effectiveness and performance of a corporation that makes research in this field begin to grow significantly in recent years. We conducted a bibliometric analysis of the BOD research from 2000 to 2021 to see the trend of publications on this subject. We retrieved a total of 635 research articles with "Board of Directors" keywords in the article title for further analysis. We used VOSviewer software to construct maps based on network data from scientific publications showing relationships between keywords, authors, countries, and journals. BOD research was dominated by authors affiliated with the United States and European institutions. In terms of co-occurrence, the top author keywords after the primary keyword were "firm performance2, "board composition", "gender diversity", "corporate governance", and "agency theory". Our results also suggest that political connection and tax avoidance may receive more attention in recent and upcoming years. To the best of the authors' knowledge, this research is the first to study the bibliometry of BOD research without any other keyword combination.
Keywords: 650; Bibliometric analysis; board of directors; research patterns and trends; Scopus; network